Fenomena Keterkaitan Kecepatan Faktual Kendaraan dengan Tingkat Pelayanan Jalan (Studi Kasus: Jalan Asrikaton, Kabupaten Malang) - Adibah, Amalia Nur; Abadi, Khoirul; Amal, Andi Syaiful; Darmawan, Azhar Adi; Sunarto, Sunarto (Universitas Batanghari Jambi, 2024)
Asrikaton street, Pakis, Malang Regency is one of the roads with moderate population density and moderate traffic flow conditions. This road is classified as a secondary arterial road and is a border road with Malang City. This road has a length of 1,200 m and a pavement width of 9 meters, with a road type of two undivided lanes (2/2 UD). This study aims to observe and assess the phenomenon of the relevance between the degree of saturation and various types of light vehicle speeds of a road. The traffic volume is 6436 vehicles/hour with a low side obstacle classification, and the degree of saturation shows that the road conditions are still relatively smooth. The maximum traffic flow volume of 2039.95 smp/h occurred at 06:45-07:45 WIB. with a low side obstacle class (equivalent value 198.7), resulting in a degree of saturation of 0.66. The most significant relevance between degree of saturation and vehicle movement speed is journey speed with the equation y = -1196.9x3 + 2008.6x2 - 1095.1x + 234.37, the coefficient of determination of 0.8867.